Hormonal and neuroendocrine responses and training adaptations following 8-weeks of preseasonal preparation period in young high-level soccer players - Hadjicharalambous, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Various hormonal responses to training-stress are measured for examining training adaptations particularly in adults` athletes. However, little information is available regarding hormonal and neuroendocrine responses to intense pre-seasonal preparation training in young athletes, in particular in youth soccer-players. The purpose therefore of the present study was to examine neuroendocrine and selected hormonal responses and their association with physiological adaptations to 8-weeks of pre-seasonal preparation training in young high-level male soccer-players. Methods All anthropometric measurements, physical fitness components and neuroendocrine and hormonal responses of eighteen (n = 18) welltrained players were evaluated in three occasions: at base-line, immediately prior to the initiation of preparation period (pre-conditioning) and 48-hours following the completion of the 8-weeks` training program (post-conditioning). Results: Total IGF-1, growth hormone (GH), plasma testosterone (T) and cortisol (C) and T:C ratio were not different between assessments but plasma prolactin (Prl) (p = 0.001) was significantly lower at post-training period. Body weight (p = 0.349), BMI (p = 0.266), resting systolic (p = 0.230) and diastolic (p = 0.527) blood pressure and sit and reach flexibility (p = 0.61) were not different among measures but HRmax (p = 0.014) was significantly lower at post-conditioning evaluation. Body fat percentage (%) (p = 0.0005) was lower and aerobic capacity (p = 0.0005), leg explosiveness (p = 0.0005), and muscular endurance [1 min-sit-ups (p = 0.001) and 1 min-push-ups (p = 0.029)] were improved by the end of preparation period. There was a significant negative correlation between endurance capacity and resting plasma Prl levels. No correlation was observed between plasma IGF-1, GH, T, C and the other fitness components, which all were examined separately. Discussion: The present study suggests that although the overload pre-seasonal training program improved soccer-specific fitness components of young high-level soccer players, several selected hormonal responses (e.g. total IGF-1, GH, plasma T and C and T:C ratio) were not influenced by the pre-seasonal training program with the exception of the reduction in resting plasma Prl concentration. Consequently, this response may reflect an increase in brain serotonergic system adaptations and/or tolerance to intense soccer pre-seasonal training. The present study provides preliminary evidence for using resting levels of plasma Prl as an indicator for training adaptations to pre-seasonal preparation period in young sub-elite soccer players.